Organization of Multinational Activities and Ownership Structure - Christian Mugele; Monika Schnitzer (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2006)
We develop a model in which multinational investors decide about the modes of organization, the locations of production, and the markets to be served. Foreign investments are driven by market-seeking and cost-reducing motives. We further assume that investors face costs of control that vary among sectors and increase in distance. The results show that (i) production intensive sectors are more likely to operate a foreign business independent of the investment motive, (ii) that distance may have a non-monotonous effect on the likelihood of horizontal investments, and (iii) that globalization, if understood as reducing distance, leads to more integration.
urn:nbn:de:bvb:19-epub-13453-5
Keywords: F23; L24; L22; L23; D23; 330; Multinational firms; Joint ventures; Distance; Technology spillovers; Ownership structure